Fabrication of Ag@Au (core@shell) nanorods as a SERS substrate by the oblique angle deposition process and sputtering technology. Issue 44 (9th August 2021) - Sha, Pengxing; Su, Qingqing; Dong, Peitao; Wang, Tianran; Zhu, Chushu; Gao, Weiye; Wu, Xuezhong
Abstract : A highly sensitive, repeatable and stable Ag@Au core–shell nano-rod array SERS substrate was successfully prepared using the OAD process and sputtering technology which proves great potential in the field of biochemical sensing. Abstract : Gold (Au) and silver (Ag) are the main materials exhibiting strong Surface-Enhanced Raman Scattering (SERS) effects. The Ag nano-rods (AgNRs) and Au nano-rods (AuNRs) SERS substrates prepared using the technology of the oblique angle deposition (OAD) process have received considerable attention in recent years because of their rapid preparation process and good repeatability. However, AgNR substrates are unstable due to the low chemical stability of Ag. To overcome these limitations, an Ag@Au core–shell nano-rod (NR) array SERS substrate was fabricated using the OAD process and sputtering technology. Moreover, simulation analysis was performed using finite-difference time-domain calculations to evaluate the enhancement mechanism of the Ag@Au NR array substrate. Based on the simulation results and actual process conditions, the Ag@Au core–shell NR array substrate with the Au shell thickness of 20 nm was studied. To characterize the substrate's SERS performance, 1, 2-bis(4-pyridyl)ethylene (BPE) was used as the Raman probe. The limit of detection of BPE could reach 10 −12 M. The Ag@Au NR array substrate demonstrated uniformity with an acceptable relative standard deviation. Despite the strong oxidation of the hydrogen peroxide (H2 O2 ) solution, the Ag@Au NR array substrate maintains good chemical stability and SERS performance. And long-term stability of the Ag@Au NR substrate was observed over 8 months of storage time. Our results show the successful preparation of a highly sensitive, repeatable and stable substrate. Furthermore, this substrate proves great potential in the field of biochemical sensing.